2014
DOI: 10.1002/ejic.201402905
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Morphological Transformations of In–MIL‐68‐Based Hexagonal Lumps to QMOF‐2‐Based Pointed Hexagonal Rods by Means of Destruction and Reconstruction Processes

Abstract: Simple thermal treatment of three‐dimensional Kagomé‐like [In(OH)(BDC)]n (In–MIL‐68) hexagonal lumps in the presence of an extra amount of 1,4‐benzenedicarboxylic acid (H2BDC) induces structural and morphological transformations of the hexagonal lumps into three‐dimensional quartz‐structured [InH(BDC)2]n (QMOF‐2) pointed hexagonal rods. Transformation processes have been monitored by scanning electron microscopy to verify the destruction of the In–MIL‐68‐based hexagonal lumps and the simultaneous reconstructio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…28 The structural and morphological transformation of MIL-68(In) to QMOF-2 by a thermal treatment (100°C) in the presence of an excess of TPA (dissolved in N, N-dimethylformamide, DMF). 29 The crystal growth of NH 2 -MOF-235 in a solution of Al 3+ and terephthalate ions in DMF led to the formation of NH 2 -MIL-101IJAl) when the temperature was increased. 30 NH 2 -MIL-88BIJFe) can undergo a reversible transformation into NH 2 -MIL-53IJFe) upon caffeine encapsulation and release.…”
mentioning
confidence: 99%
“…28 The structural and morphological transformation of MIL-68(In) to QMOF-2 by a thermal treatment (100°C) in the presence of an excess of TPA (dissolved in N, N-dimethylformamide, DMF). 29 The crystal growth of NH 2 -MOF-235 in a solution of Al 3+ and terephthalate ions in DMF led to the formation of NH 2 -MIL-101IJAl) when the temperature was increased. 30 NH 2 -MIL-88BIJFe) can undergo a reversible transformation into NH 2 -MIL-53IJFe) upon caffeine encapsulation and release.…”
mentioning
confidence: 99%
“…For example, it is reported that structural and morphological transformation of bulk MOFs between QMOF-2 and In-MIL-68 was achieved by adjusting the amount of MOF precursors. 14 To date, structural transformation as well as morphological transformation in 2D MOF frameworks has not been investigated well. Additionally, having the ability to control accurately over its shape and structure is highly required, but it remains a huge challenge in the development and application of 2D MOFs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…units) intensity (arb. units) 20 30 analogous structural transformation from MIL-68(In) to QMOF-2, and verified that MIL-68(In) is an initial kinetic product and QMOF-2 is a final thermodynamic product of In 3þ with an excess amount of H 2 BDC [25]. To verify the tenability of this conclusion in In 3þ and H 2 BDC_NH 2 system, the amount of the ligand was continuously increased to M : L ¼ 1 : 6, and the reaction time was prolonged to 24 h. The PXRD result validates that exclusive QMOF-2 is formed.…”
Section: Structure Transformation Analysismentioning
confidence: 62%
“…But, the Bragg peak assigned to QMOF-2 can be obviously observed in the PXRD spectra of M : L = 1 : 3, which indicates that disparate structural transformation process is taking place with an excess amount of H 2 BDC_NH 2 . Choi and co-workers reported the analogous structural transformation from MIL-68(In) to QMOF-2, and verified that MIL-68(In) is an initial kinetic product and QMOF-2 is a final thermodynamic product of In 3+ with an excess amount of H 2 BDC [25]. To verify the tenability of this conclusion in In 3+ and H 2 BDC_NH 2 system, the amount of the ligand was continuously increased to M : L = 1 : 6, and the reaction time was prolonged to 24 h. The PXRD result validates that exclusive QMOF-2 is formed.…”
Section: Resultsmentioning
confidence: 96%